Research Methods Deserve Credit and Recognition as a Valuable Research Output - Ganley, Emma (Septentrio Conference Series, 2020)
See RECORDING (starts at 00:32:25). Open Research and improved mechanisms to assess and evaluate researchers are both things needed for the scholarly enterprise. We now commonly see open access to research articles, data and code, and citations, which together have moved the needle for achieving both Open Research and research assessment/evaluation. However, one key element that is missing, which is a cornerstone of the research process, is access to a granular description of the methods and approaches used to perform the research. The methods, approaches, and protocols are often incredibly painstaking to develop and optimize and are the key piece needed to fully interpret the results and ensure reproducibility. Too often sufficient information about methods is missing from research articles; the Cancer Biology reproducibility project that aimed to reproduce fifty research studies was stopped after just eighteen were attempted because the efforts to understand what experiments were used was a “hopeless slog”. The research community must incorporate better research method documentation before, during, and after publication to ensure that research efforts are replicable and that the methods can be valued as a standalone research output. protocols.io is a platform, tool, and repository for collaborative method development, storage, and open access publication, which provides an ideal solution to this challenge. By publishing the methods and ensuring they have their own DOIs, any reuse and citations can be tracked and incorporated into research assessment and evaluation processes. Researchers who successfully develop and optimize research protocols deserve to receive credit for this as a distinct output alongside the overarching write-up presented in a manuscript and resulting data.